A Theoretical Research on the Impact of Pyridine Based and Fused Cyclic Based Polymer on the Properties of Donor Polymer for Organic Solar Cells (Communications in Computational Chemistry, 2022)
The polymer with D-A structure has been certified a significant role as donormaterials of organic solar cells (OSCs) for its outstanding light absorption. In this work,the properties of pyridine based and fused cyclic based D-A polymer was studied bymeans of DFT and TD-DFT theory under PBE0/6-31G(d) level. Based on the reportedpolymer D1, pyridine and fused cyclic were introduced to D2, D3 and D4. Comparedwith polymer lacking the pyridine and fused cyclic, the pyridine and fused cyclic basedexhibits better planarity, lower HOMO energy and broader absorption properties,which are helpful to get a higher $V_{oc}$ and $J_{sc}$. Moreover, fused cyclic based as well aspyridine monocycle and pyridine fused cyclic based polymer shows the ability toenhance the hole transfer rate. Hence, the approach of introducing pyridine and fusedcyclics to polymer donor is a feasible way to modulate the electron-withdrawingcapability in D-A polymer chain thereby promotes the performance of the OPV devices.